PRODUCTIVITY ANALYSIS IN THE MANUFACTURE OF DIE PLATE PRODUCTS USING THE OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD AT PT. XYZ - Septiana, Reski; Fauzan, Ghazi; Yusuf, Yusvardi; Ula, Shofiatul; Demustila, Harly; Hernadewita, Hernadewita; Hendra, Hendra; Setiawan, Ipick (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The effectiveness possessed by manufacturing machines is a parameter used to determine the performance of a company's manufacturing process. Effectiveness can be shown in the form of percentages as effective as a manufacturing process is carried out. Effectiveness can be a reference for companies in the implementation of production by evaluating charts of production that are considered less effective and do not meet standards. The factors that affect the effectiveness of a production machine can be seen in the availability or capability, quality, and performance where in this article the overall equipment effectiveness (OEE) method which has a production period of one month is used to get the effectiveness of the production process carried out. The results obtained in this study were 88.53% in the first week of proposition, 94.63% in the second week of production, and 91.58% in the third and last week of production.